Variations and influence factors of 210Pb-specific radioactivity in modern calcite depositions in a subtropical cave, South China. (February 2020) - Tang, Wei; Lan, Gaoyong; Yang, Hui; Yin, Jian-Jun; Pu, Junbing
Abstract: Although 210 Pb dating has been successfully used in speleothems, the understanding of the factors impacting 210 Pb variations in modern calcite depositions in karst caves is poor due to the lack of in situ monitoring. Here, we studied the 210 Pb variations in drip water and modern calcite depositions at five sampling sites in Maomaotou Big Cave in Guilin, south China, through more than three years of in situ monitoring. In this work, the air 222 Rn concentrations, weights and 210 Pb-specific radioactivity of modern calcite depositions showed significant temporal and spatial variations. The modern calcite deposition weights and 222 Rn concentrations in the air of Maomaotou Big Cave ranged from 0.02 to 6.04 g and 62.9–628 Bq.m −3 (higher values in summer-autumn and lower values in winter–spring), respectively, while the 210 Pb-specific radioactivities in calcite depositions varied from 7.33 to 658.52 Bqkg −1, with lower values reported in summer–autumn and higher values in winter–spring. The opposite seasonal trends observed for the 222 Rn concentrations and 210 Pb-specific radioactivity indicated that the air 222 Rn concentration was not the dominant factor influencing the 210 Pb-specific radioactivity in the modern calcite depositions. This study concluded that 210 Pb-specific radioactivity in modern calcite depositions is mainly carried by drip water; further, the remarkable negative correlation between deposition weight and 210 Pb-specific radioactivity in modern calcite depositions suggests that the Constant Initial Concentration model (CIC) is fit for recent speleothem dating in a closed system. Such important information may provide a scientific basis for cave deposition dating using 210 Pb. Highlights: First in situ monitoring on 210 Pb-specific radioactivity of modern calcite depositions. 210 Pb-specific radioactivity showed significant temporal and spatial variations. Deposition weight and coeval 210 Pb-specific radioactivity showed a negative correlation.